Comorbidity of depression and metabolic syndrome: on the question of causal or associative connections - N. N. Petrova; N. V. Semenova; L. V. Malyshko (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The problem of frequent comorbidity between depression and metabolic syndrome has been known to medicine for a long time. However, there is more and more data on the joint course of these states. The narrative review presents current scientific data on the relationship between metabolic syndrome and depression, as well as the results of studies on the effect of antidepressants on the development of metabolic disorders. The review is based on an analysis of 75 publications published in the bibliographic databases of the RSCI and Medline. Despite numerous research results proving the comorbidity of depression and metabolic syndrome, the question of their causal relationship remains open. The presented materials complement the understanding of the associations of metabolic syndrome and depression, and also allow us to take into account the mechanisms of comorbidity of these conditions when choosing antidepressants.